2017
DOI: 10.48550/arxiv.1706.00633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Robust Detection of Adversarial Examples

Abstract: Although the recent progress is substantial, deep learning methods can be vulnerable to the maliciously generated adversarial examples. In this paper, we present a novel training procedure and a thresholding test strategy, towards robust detection of adversarial examples. In training, we propose to minimize the reverse crossentropy (RCE), which encourages a deep network to learn latent representations that better distinguish adversarial examples from normal ones. In testing, we propose to use a thresholding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Label smoothing. Label smoothing improves the generalization [38,32] and robustness [31,19,35] of a deep neural network. Label smoothing replaces one-hot labels with smoothed labels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Label smoothing. Label smoothing improves the generalization [38,32] and robustness [31,19,35] of a deep neural network. Label smoothing replaces one-hot labels with smoothed labels.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that label smoothing has similar effect as randomly replacing some of the ground-truth labels with incorrect values at each mini-batch [46]. [31] proposes reverse cross entropy for gradient smoothing. It encourages a model to better distinguish adversarial examples from normal ones in representation space.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, given an input x, this metric computes an estimation of the uncertainty of a deep Gaussian process [5], using the outputs of multiple DNNs with the same architecture that are trained in the same training set but using the dropout Using this metric we expect a higher uncertainty estimation when the input x is an adversarial input. Also a training procedure that can enhance the detection results when we use the kernel density estimation as a metric is proposed in [14]. This training procedure adds a regularization term called reverse cross-entropy.…”
Section: Detecting Adversarial Examplesmentioning
confidence: 99%
“…It Analysis process. To start the analysis, we calculated an adversarial score for each image [39]. A high score means the image is most probably to be an adversarial example.…”
Section: Analyzing White-box Adversarial Examplesmentioning
confidence: 99%